Analysis of the Capacity and Effectiveness of Urban Drainage System - Jody Martin Ginting; Pardosi, Elisa; Sri Anggraeni (Journal of Civil Engineering and Planning (JCEP), 2025)
This study evaluates the drainage capacity of Ocarina Road, Batam City. Hydrological analysis using three probability distributions shows that the Generalized Extreme Value (GEV) distribution is the most appropriate based on the Kolmogorov–Smirnov test. The 25-year return period design flow calculated using the Rational Method is 1.546 m³/s, while the capacity of the existing U-ditch channel is only 1.17 m³/s. Validation using HEC-RAS shows water levels approaching the channel edges, confirming that the hydraulic capacity is inadequate. The channel also does not meet the 0.25 m safety height standard for discharge of 1.5–5.0 m³/sec according to KP-04 of the Directorate General of Water Resources. These results indicate that the channel capacity is inadequate, requiring an increase in channel dimensions or the addition of supporting infrastructure to reduce the risk of flooding.